A systematic scoping review of determinants of multidisciplinary cancer team access and decision-making in the management of older patients diagnosed with colorectal cancer. Issue 6 (July 2020) - Holden, Carol A.; Poprawski, Dagmara; Singhal, Nimit; Buckley, Elizabeth; Caruso, Joanna; Wichmann, Matthias W.; Price, Timothy
Abstract: Early diagnosis of colorectal cancer (CRC) and access to optimal treatment achieves optimal cancer outcomes. However, CRC survival inequalities persist with a lower survival rate for older patients (≥65 years). Although the reasons for poorer cancer survival in older people are complex, evidence suggests that these patients are less likely to receive best practice care as indicated by access to multidisciplinary team (MDT) care. Three electronic databases were systematically searched to examine factors that affect access to, and clinical decision-making, in the context of MDT care of older people with CRC. We included studies reporting empirical data relating to predictors for a patient's case being discussed at a MDT meeting and/or factors that impact treatment decision-making during the meeting. From 303 returned titles and abstracts, eighteen articles were reviewed. Eight studies specifically selected older patients, with eligibility criteria varying from ≥65 to ≥80 years. Five articles explored predictors of MDT access, with all articles identifying age as a negative, and advanced stage as a positive predictor of MDT discussion. Fourteen studies explored factors that influenced the MDT decision-making process, with older age and presence of comorbid disease negatively influencing treatment decisions (cases less often discussed and/or treatment not recommended). A few studies identified access to a MDT discussion as an independent predictor for CRC treatment. Access to the MDT process for older patients with a CRC diagnosis should be based on relevant geriatric domains rather than on chronological age alone, which is expected to allow more appropriate clinical decision-making and reduce treatment inequities for older patients with cancer.